2016
DOI: 10.3184/003685016x14773090197706
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and Analytical Assessment of E-Cigarette Refill Components on Airway Epithelia

Abstract: There are over 2.6 million users of e-cigarettes in the United Kingdom alone as they have been promoted as a safer alternative to traditional cigarettes. The addition of flavours and aromas has also proven to be popular with younger generations. In this review, we survey the range of studies in the short timeframe since e-cigarettes reached the market to draw attention to the health associated risks and benefits of their introduction. We complement this review with a case study reporting on the composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 86 publications
(49 reference statements)
2
14
0
Order By: Relevance
“…Mystery Mix, a selection from the “menthol” category, showed significant cytotoxicity. This is consistent with other in vitro studies in which other investigators have found significant cytotoxicity with menthol flavoring aerosol exposures on epithelial cell lines (Leigh et al, 2016 ; Singh et al, 2016 ). Mixing equal proportions of e-liquids from 10 differently flavored e-liquids gave rise to the highest cytotoxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Mystery Mix, a selection from the “menthol” category, showed significant cytotoxicity. This is consistent with other in vitro studies in which other investigators have found significant cytotoxicity with menthol flavoring aerosol exposures on epithelial cell lines (Leigh et al, 2016 ; Singh et al, 2016 ). Mixing equal proportions of e-liquids from 10 differently flavored e-liquids gave rise to the highest cytotoxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have demonstrated that nicotine concentrations in e-liquids are often considerably different to the concentrations listed on the labels 169,[173][174][175][176][177][178][179][180][181][182][183][184] (Supplementary Table 6).…”
Section: Incorrect Nicotine Concentration Labelingmentioning
confidence: 99%
“…Electronic cigarettes (e-cigs) are electric devices which have become very popular worldwide in the last decade [ 1 , 2 ]. Their popularity among the smokers’ community has grown exponentially, so that e-cigs have become a leading product among the various alternatives to traditional cigarettes.…”
Section: Introductionmentioning
confidence: 99%